State Policies and The Increasing Number of Atheism in The Middle East: A Case Study of Saudi and Turkey - Yuangga Kurnia Yahya (Arabic Literature Department, 2022)
This study aims to see the correlation between state policies and the increasing number of atheism in Turkey and Saudi Arabia. These two countries were chosen because they represent two countries with a majority Muslim population that apply Islamic law and treat atheism differently. Using LeDrew's trajectory to atheist conversion perspective, this study attempts to explore the correlation between the two. This study shows that both secular country and Islamic kingdoms have the same potential in the phenomenon of conversion to atheism. This is supported by various things that encourage them to be skeptical of religion such as women's issues, violence, discrimination, and so on brought by The New Atheist. The existence of social media assistance also helps atheists to declare themselves as atheists in cyberspace.